Pemberdayaan Fatayat NU Kota Bogor Melalui Workshop Sabun Padat - Adrinoviarini, Adrinoviarini; Nanda, Ririn Fatma; Febrianto, Dony; Pratama, Yogi (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
The target of the solid soap workshop community empowerment is the Fatayat NU in Bogor City. The needs of the actors of change (members of Fatayat NU Bogor City) in the form of normative needs can be met by the target community (Fatayat NU Bogor City) with the efforts of the target community to seek various services for their members through solid soap workshops is active involvement in fulfilling basic needs household. The solid soap workshop is tailored to the needs of the community who use soap for their daily needs. Solid soap workshops use materials and tools that are cheap and easy to find in households, namely: cooking oil, caustic soda, fragrance, scales and soap molds. Workshop participants were representatives of 6 PAC Fatayat NU Bogor City. The workshop was held at the Integrated Laboratory of the Faculty of Engineering and Computer Science (FTIK) Nahdlatul Ulama University of Indonesia (Unusia). The resource persons came from lecturers from the Unusia Agro-Industry Technology Study Program assisted by 2 students. The method used in carrying out the service was counseling and practice on how to make solid soap. The workshop participants will receive a module on how to make soap, training on making soap and soap made by each participant. After the workshop is finished, an evaluation will be carried out by distributing questionnaires to the workshop participants to find out how far the effectiveness of the workshop is and the level of satisfaction of the participants in the soap making workshop. evaluation through a questionnaire obtained the following results: (1) 92.3% of participants could easily accept and understand the solid soap workshop material; (2) 76.9% of participants stated that the resource person mastered the workshop material well; and (3) 69.2% of participants stated that the training material n delivered in order and clearly systematically. From the questionnaire it was also known that the workshop participants hoped that there would be other empowerment workshops that would support the economic independence of the participants. In general, the hope of this empowerment is to fulfill basic household needs that can be fulfilled on their own in a sustainable manner so as to foster economic independence and improve people's welfare.